FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Nurul Aghniyak; Ika Wahyuni; Dwi Perwitasari Wiryaningtyas (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Increasing competition in the era of globalization requires companies to adapt and effectively manage critical functions to maintain their competitive advantage. This study aims to analyze the factors influencing capital structure, both partially and simultaneously, and to identify the most dominant variables in manufacturing companies listed on the Indonesia Stock Exchange. The variables used include asset structure, profitability, company size, liquidity, and growth. The research method employed classical assumption tests, multiple linear regression, t-tests, F-tests, dominance tests, and coefficients of determination. The regression results show the following equation: Y = 255.349 + 0.176X1 – 0.513X2 – 0.057X3 – 0.160X4 + 0.638X5 + e. Based on the t-test, asset structure (calculated t = 0.375 < 2.02269), profitability (calculated t = -1.757 > -2.02269), and firm size (calculated t = -1.520 > -2.02269) had no partial effect on capital structure. Meanwhile, liquidity (calculated t = -4.166 < -2.02269) and growth (calculated t = 2.646 > 2.02269) had a significant partial effect on capital structure. The F-test results showed F-calculated = 7.434 > F-table = 2.45, indicating that all independent variables simultaneously had a significant effect on capital structure. Based on the dominance test, liquidity (X4) had the greatest influence, with a value of -4.166, compared to the other variables. The coefficient of determination (R²) of 0.488 indicates that 48.8% of the variation in capital structure can be explained by independent variables, while the remaining 51.2% is influenced by other factors outside this study.